Liang zi ji suan ji bian cheng : cong ru men dao shi jian - Johnson, Eric R.; Harrigan, Nic; Gimeno-Segovia, Mercedes (O'Reilly Media ; Ren min you dian chu ban she, 2021)
Detailed summary in vernacular field.